The Quest for QWERTY - Hossain, Tanjim; Morgan, John (American Economic Review, 2009)
In settings ranging from office suite software to online auctions, casual empiricism suggests a strong tendency for markets where platforms compete to tip to a single dominant player. But which platform will prevail? One might hope that the better platform will be selected. Theory, however, offers no such comfort. Standard models suggest that tipping to any platform—even an inferior one—comprises an equilibrium. Paul A. David (1985) suggests that getting stuck in a bad equilibrium is not merely a theoretical possibility, but a good description of what happened in the typewriter keyboard market. He argues that the QWERTY arrangement prevailed (and continues to prevail) despite its inferiority to the DVORAK arrangement. The essence of David’s argument is that, by virtue of its head start in the market, users expected QWERTY to prevail and these expectations were selffulfilling. As a consequence, the superior platform, DVORAK, was never adopted. The idea that self-fulfilling expectations can lead an inferior platform to triumph in the face of better alternatives has now become standard in the economics literature and features prominently in many textbooks (see, for instance, Luis M. B. Cabral, 2000). Yet, despite the long passage of time since David’s piece was first published, the datedness of the examples illustrating this idea is striking. Most textbooks, including Cabral’s, are content to focus on QWERTY as well as the competition between Betamax and VHS some thirty years ago. We thank Dylan Minor and Xingtian Zhu for excellent research assistance. We gratefully